A five year learning experience with sequence of events in a child with closed femur shaft fracture - Kulkarni, Shrihari L.; Mannual, Sunil; Daragad, Manjunath; Patil, Naveenkumar; Sharan, Prateek M. (International Journal of Research in Orthopaedics, 2021)
Femur shaft fractures are the most common fractures requiring hospitalization in children. Management of these fractures mainly depend on the age of the child. Associated injuries, fracture pattern, weight of the child and overlying soft tissue condition also influence the management. Still, the definitive treatment remains controversial in children between 5-16 years. We present our experience in management of 5 year old boy with mid shaft femur fracture and its complications. In his paper we want to highlight the importance of sticking to the basic principles and the recommendations in the management of the paediatric femur shaft fractures.